Changes in Quinoa Seed Fatty Acid Profile Under Heat Stress Field Conditions - Matías, Javier; Rodríguez, María José; Granado-Rodríguez, Sara; Cruz, Verónica; Calvo, Patricia; Reguera, María (Frontiers in Nutrition, 2022)
The nutritional quality of quinoa is often related to the high protein content of their seeds. However, and despite not being an oilseed crop, the oil composition of quinoa seeds is remarkable due to its profile, which shows a high proportion of polyunsaturated fatty acids (PUFA), particularly in essential fatty acids such as linoleic (ω-6) and α-linolenic (ω-3). In line with this, this work aimed at evaluating the effect of elevated temperatures on the oil composition of different quinoa cultivars grown in the field in two consecutive years (2017 and 2018). In 2017, heat stress episodes resulted in a reduced oil content and lower quality linked to decreased ratios of oleic acid:linoleic acid, larger omega-6 (ω-6) to omega-3 (ω-3) ratios, lower MUFA and higher PUFA contents. Furthermore, the correlations found between mineral nutrients such as phosphorous (P) and the contents of oleic and linoleic acids emphasize the possibility of optimizing oil quality by controlling fertilization. Overall, the results presented here show how the environmental and genetic factors as well as their interaction, may impact on oil quality in quinoa seeds.